Zavarovanje jamstev iz prodajne pogodbe - Frantar, Marko (Pravni letopis, 2020)
A sale and purchase agreement (SPA) negotiated in the context of an M & A transaction will typically include a set of seller`s representations and warranties (R&W) around the object of sale. A breach of R&W can entitle the purchaser to seek indemnification from the seller for any resulting loss. R&W serve the purpose of allocating certain risks to the seller. Understandably, the parties will have different positions on the scope of R&W. The purchaser will want to see a wide R&W catalogue, while the seller will wish to narrow its scope to the maximum extent possible. Warranty and indemnity (W&I) insurance can assist in bridging the gap between parties` expectations around the scope of R&W. W&I insurance effectively allows for transferring the risk of liability for breach of R&W to an insurer. This can have a significant impact on the course of SPA negotiations.
Keywords: jamstvo; obligacijsko pravo; pogodbeno pravo; prodajne pogodbe